Characteristics of the disbelievers in the first Surah Al - Baqarah - An analytical study - Muqden, Salah Ali (Journal of Islamic Sciences, 2019)
The Quran is the first source, which is the word of God, which is incapable of all creation of the type, and hence the status of the science of interpretation because it relates to the book of God, and the status of analytical study in the Koran, and the highlight of the Quranic miracle in most aspects was the reason for my choice for this subject In order to know the characteristics of the unbelievers came the research entitled (qualities of the unbelievers in the first Surah Al-Baqarah - an analytical study)It is written in accordance with the analytical method by its known and reliable steps, which is very important because the research shows the faces of Quranic miracles in all its developed aspects, especially reliance on sources and references in the presentation of opinions in interpretation and interpretation. The most prominent opinion was the interpretation of some places and things that bear Opinion, particularly in the stereotypical-graphical-stylistic subjects.
Keywords: Characteristics of the unbelievers; Surat al - Baqarah; interpretation; attributes and names; the first cow